The Self-perceived Impact of COVID-19 Human Mobility Restrictions on Armenian Students Aged 14-18 - Poghosyan, Garik (Journal of Education in Black Sea Region, 2021)
The present article showcases the self-perceived impacts of COVID-19-related human mobility restrictions on the Armenian youth aged 14 to 18. Rather than attempting to discuss policies or theories or concentrate on certain areas of the fabric of human society, such as human rights, economy, health care, this case study makes a bold attempt to illuminate the reader about the condition and self-perceived effects of the crisis on a specific age group in the context of COVID-restricted mobility and ensuing challenges (education, social life, including sports and extracurricular activities, emotional well-being) in a given country, something that has been prevailingly, if not completely, ignored even in those research projects that have addressed the COVID-19-related human mobility limitations for specific groups of people (migrants, the displaced, women, etc.). Thus, the author has attempted to lay the groundwork for further case studies as well as comparative research investigating the human mobility dimension of the COVID-19 crisis for adolescents or various age groups with an emphasis on the effects of reduced or restricted mobility on the intellectual, athletic, social or cultural life of those affected by them. Overall, the participants displayed the whole gamut of both negative and positive experiences and gave varied responses. Keywords: human mobility, COVID-19, students aged 14-18